Perceptions of Gender Equality among Icelandic Year 10 Adolescents: Population Studies 1992, 2006, and 2014 - Einar Baldvin Thorsteinsson; Andrea Sigrún Hjálmsdóttir; Thoroddur Bjarnason (MDPI AG, 2021)
The aim of this research is to outline, for the first time, the changes in attitudes towards gender equality among 10th graders in Iceland based on data obtained from the Health Behaviour in School-aged Children (HBSC) in 1992, 2006, and 2014. The sampling proportions were high (85.1% in 1992, 43.2% in 2006, and 77.9% in 2014), thereby reflecting parameters (population values) rather than statistics (sample values). Boys and girls are viewing gender roles as being more equal with time, while, concurrently, girls tend to have more gender-equal attitudes than boys. The present paper provides an unparalleled examination of changes in attitudes towards gender equality. After a backlash in adolescents' attitudes, revealed in the 2006 study, there are positive signs of more gender-equal attitudes in the 2014 results.